Public engagement can change your research, but how can it change your research institution? ICES Case Study - Paul, Jenine; Davidson, Randy; Johnstone, Cheryl; Loong, Margaret; Matecsa, John; Guttmann, Astrid; Schull, Michael J (International Journal of Population Data Science, 2020)
This article explores the approach that ICES (formerly the Institute for Clinical Evaluative Sciences) uses to encourage public engagement at both the research study and corporate level. ICES is an independent not-for-profit research institute in the province of Ontario, Canada. This article was co-written by ICES’ public engagement team and four members of the ICES Public Advisory Council (PAC). As part of the process of writing this article PAC members provided their reflections on why they got involved, what worked well and the limitations and challenges of ICES’ approach. ICES described the development of its public engagement strategy to inform how the institution would capture and incorporate the values of Ontarians in ICES activities and research. ICES provided details on two key elements of its strategy: the formation of a PAC to advise its leadership, and the creation of resources and supports to encourage researchers to incorporate public engagement in their projects. PAC members and ICES provided perspectives on what impact they perceive as a result of the public engagement strategy. PAC members expressed that ICES has demonstrated listening to and using their input, but it is too early to evaluate if their feedback has changed the way ICES conducts its work. ICES discussed the challenges and successes in building and implementing the public engagement strategy, including recruiting a diverse council, aligning with public priorities and creating a culture of engagement. As a result of public input, ICES has restructured the way the institution explains its privacy and cybersecurity approach to build trust and confidence. ICES has also seen an increase in researchers using public engagement resources, and early data suggests that in 2019 about 20% of scientists included some form of public engagement in their projects. ICES’ journey to public engagement resulted in important changes to processes and activities at the institution, but there is much more that needs to be done. PAC members advocate that public members should be engaged in health data research and hope that public input will be a core element in health data research in the future. ICES will continue its efforts to address public priorities and will seek to further evaluate the impact of public engagement across the organisation.